Lubaina Himid - Wellen, Michael (Tate Publishing, 2021)
Introduction / Michael Wellen -- On the pleasures of opera / Griselda pollock in conversation with Lubaina Himid -- To build otherwise / Amrita Dhallu -- Epiphanies through dress / Carol tulloch -- Some thoughts from the artist on clothes and pattern -- The exhibit as theatre / Lisa Merrill -- Composing with paint and sound / Christine Eyene in conversation with Lubaina Himid and Magda Stawarska-Beavan -- What happens in the studio / Micahel Wellen
Impressum: First published 2021 by order of the Tate Trustees ... on the occasion of the exhibition "Lubaina Himid", Tate Modern, London, 25 November 2021-3 July 2022; Musée cantonal des Beaux-Arts, Lausanne / Plateforme 10, 3 November 2022-5 February 2023
Includes bibliographical references
Keywords: Himid, Lubaina -- 1954-; Malerei; Himid, Lubaina / 1954- / Exhibitions; Himid, Lubaina; Ausstellungskatalog -- Tate Modern -- 25.11.2021-03.07.2022 -- London; Ausstellungskatalog -- Musée cantonal des Beaux-Arts -- 03.11.2022-05.02.2023 -- Lausanne; Bildband